The Impact of Combination of Ozonation and Ultrasonication Process on Morphological and Chemical Properties of κ-Carrageenan - Nurfiningsih Nurfiningsih; Ratnawati Ratnawati; Aji Prasetyaningrum (Reaktor, 2019)
Carrageenan application in the biomedical field is influenced by the size of molecular weight. Depolymerization process is needed for changing the high molecular weight (HMW) fraction of κ- carrageenan into low molecular weight fraction (LMW) of κ- carrageenan. Ozone is a powerful oxidant and considered for depolymerization of κ- carrageenan. This research was conducted as an investigation on the influence of the combination of ozonation and ultrasonication (OZ/US) on the chemical and morphological characteristics of κ-carrageenan. FTIR and Scanning electron microscopy (SEM) was used to determine the change of chemical and morphological characteristics of κ-carrageenan. The result of this study showed that there was no change of chemical properties of κ-carrageenan during OZ/US treatment. The sulfate content was obtained after OZ/US treatment tends to be stable.  Nevertheless, the result of SEM analysis showed that there were changes on morphological characteristics of κ-carrageenan after OZ/US treatment.  Keywords: ultrasonication, κ-carrageenan, ozonation, morphological, chemical